Review of the book Food Regimes and the Agrarian Question: Regimes alimentares e questões agrárias - França, Andreya Raquel Medeiros de (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2019)
Seeking to discuss issues of rising food production, Professor Philip McMichael, from the Cornell University's Department of Developmental Sociology, writes the book Food Regimes and the Agrarian Question to analyze the development of capitalism in agriculture through of the concepts of food regimes and agrarian questions, positioning food as a central factor, without questioning the relevance of the dispute over land. Divided into two parts, the first is subdivided into three chapters that discuss the idea about food regime and its historical aspects. In his second part, the author resumes the discussion about the food regime, building a parallel of the three cycles of the regime and its transitions, exposing the repercussions in distinct regions, East Asia, Latin America and the Middle East. Finally, the wide debate of the work on the agrarian world, from a historical perspective and rich in empirical cases, also ignites the discussion about food sovereignty, and the directions that it has taken, making us question what is the social role of food.Keywords: food regimes; agrarian question; food.MCMICHAEL, Philip. Regimes Alimentares e Questões Agrárias. São Paulo: Editora Unesp e Editora da UFRGS, 2016. 256 p. Resenha de: FRANÇA, Andreya Raquel Medeiros de. Regimes alimentares e questões agrárias. Estudos Sociedade e Agricultura, v. 27, n. 2, p. 440-444, jun. 2019.Submitted in october 2018.Accepted in february 2019.